Онтологія війни й миру в мовно-інформаційному просторі сьогодення - Коць, Т. (Культура слова, 2019)
У статті проаналізовано філософсько-оцінну парадигму мовних
засобів на позначення одвічних і актуальних в умовах сьогодення
України понять війна, мир. Простежено реалізацію в мовно-
інформаційному просторі сьогодення функціонально-стилістичного
потенціалу мови для вираження соціально-політичного і
філософського протистояння ворожих сторін в контексті поділу
цінностей на свої і чужі. Проаналізовано лексику, прецедентні
одиниці, метафори, епітети, що є показовими для сучасних
текстів ЗМК і які є виразниками лінгвософії національної суспільної
свідомості. The article analyzes the philosophical and evaluation paradigm of
linguistic means for denoting the concepts of war and peace in the context
of present-day Ukraine. The realization of the functional and stylistic
potential of language in expressing the socio-political and philosophical
opposition of hostile parties in the context of the division of values into
their own and othersʼ has been traced in the linguistic and information
space. Analyzed vocabulary, precedent units, metaphors, epithets, which
are indicative of modern texts of the Means of mass communicationand
which express the linguistics of the national public consciousness.
War in the minds of society is always associated with aggression:
destruction, distress, death, and peace with peace, peace, life. Such
perception of these phenomena is entrenched in the antonymic ratio of two
eternal words of the Ukrainian dictionary war – peace. The basic element
of their opposition is the original semantics of the word war, which
contains a contradictory feature, which is denied in the definition of peace.
The ontology of war and peace in the linguistic and informational
texts of today corresponds to the psychological attitudes of society and
is a reflection of the current socio-political situation in the country.
Around the war and peace as the nuclear concepts of the Means of mass
communicationand, a synchronous linguistic-evaluative paradigm is
formed, which is an expression of the linguistic-national consciousness,
an indicator of the philosophical comprehension of a specific time period
of the history of Ukraine in general, and of the functional capabilities of
the language in particular.